2015
DOI: 10.18242/anpscripta.2015.01.01.02.0003
|View full text |Cite
|
Sign up to set email alerts
|

Diversidad y Productividad del Estrato Herbáceo en una Sabana de la Sierra Fría, Aguascalientes

Abstract: To determine species richness, abundance, and alpha diversity indexes to estimate primary productivity and to obtain rain-use efficiency factor in the savannah ecosystem at the Natural Protected Area Sierra Fria, Aguascalientes, we collected 28 phyto-ecological samples randomly. The floristic composition was determined in an area of 256 m 2 and species abundance in a four-meter line, observing 100 points space out each four cm. We estimate diversity by the Shannon-Wienner index (H´). Four exclusions of 144 m 2… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
1
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 3 publications
(4 reference statements)
0
1
0
Order By: Relevance
“…Para obtener el listado florístico se realizaron 48 inventarios fitoecológicos en el mismo número de sitios de muestreo con cultivo maíz de temporal elegidos de manera dirigida (Castillo-Nonato & Chávez-Mejía 2013) y con previa autorización del dueño, diez por provincia biogeográfica durante el ciclo agrícola 2020, cinco en SMO y CP y ocho en AS durante 2021. Una vez en el sitio de muestreo, se utilizó el método área muestra homogénea de 256 m 2 en orden ascendente (1/64, 1/16, 1/8, 1/4, 1/2, 1, 2, 4, 8, 16, 32, 64, 128 y 256 m 2 ) (Daget & Godron 1982, Sosa-Ramírez et al 2015 y adicionalmente se registraron las especies que se observaron fuera del área de muestreo pero dentro de la parcela (Rivera-Ramírez et al 2021). Además, con el fin de analizar la diversidad de arvenses se muestreó por medio de cuadrantes al azar con base en la técnica usada por Sánchez-Blanco & Guevara-Féfer (2013).…”
Section: Materiales Y Métodosunclassified
“…Para obtener el listado florístico se realizaron 48 inventarios fitoecológicos en el mismo número de sitios de muestreo con cultivo maíz de temporal elegidos de manera dirigida (Castillo-Nonato & Chávez-Mejía 2013) y con previa autorización del dueño, diez por provincia biogeográfica durante el ciclo agrícola 2020, cinco en SMO y CP y ocho en AS durante 2021. Una vez en el sitio de muestreo, se utilizó el método área muestra homogénea de 256 m 2 en orden ascendente (1/64, 1/16, 1/8, 1/4, 1/2, 1, 2, 4, 8, 16, 32, 64, 128 y 256 m 2 ) (Daget & Godron 1982, Sosa-Ramírez et al 2015 y adicionalmente se registraron las especies que se observaron fuera del área de muestreo pero dentro de la parcela (Rivera-Ramírez et al 2021). Además, con el fin de analizar la diversidad de arvenses se muestreó por medio de cuadrantes al azar con base en la técnica usada por Sánchez-Blanco & Guevara-Féfer (2013).…”
Section: Materiales Y Métodosunclassified
“…These authors found the seeds of 18 plant species in 384 scats of mammalian carnivores, concluding that carnivores can disperse seeds in abundance and intestinal passages can have varying effects on different plant species, favoring or deteriorating the germination of their seeds, as well as dispersal to and colonization of distant areas and ecosystems. In particular, the Sierra Fría Protected Natural Area (ANP-SF) in the state of Aguascalientes, Mexico is made up of different types of ecosystems, including TF (Sosa-Ramírez et al, 2015) and DTF (Argumedo-Espinoza et al, 2018). The objective of this study was to evaluate the role of carnivorous mammals in the dispersal of seeds in different forest ecosystems, namely temperate forest and dry tropical forest.…”
Section: Introductionmentioning
confidence: 99%